Development Karaja Cards Based QR Code Integrated Augmented Reality to Improve Javanese Script Writing Skills - Ridwayanti, Anissatul Mahmudah; Sukasih , Sri (Jurnal Ilmiah Profesi Pendidikan, 2025)
The low Javanese script writing skills of students result from limited understanding of its forms and variations. This study aims to develop and test the feasibility, effectiveness, and practicality of Karaja card media based on QR Code integrated with Augmented Reality. The research employed the Borg and Gall development model. This study involved 32 grade IV students of SDN 1 Rajawana in the 2024/2025 academic year, with a small-scale trial on 9 grade IVA students and a large-scale trial on 23 grade IVB students. Data collection was carried out through tests (pretest-posttest) and non-tests in the form of interviews, questionnaires, observations, and documentation. The results of expert validation showed that this media was "very feasible" with an average score of 91.4%. Practicality was shown from the results of the teacher and student response questionnaires which gave scores of 92.5% and 91%, assessing this media as "very positive". Its effectiveness is proven through t-test (0.001 < 0.05) and N-gain 0.73 (“high” category). In conclusion, shows that QR Code-based Karaja card media with Augmented Reality is feasible, practical, and effective in improving grade IV Javanese script writing skills.